Combination therapy only shows short-term superiority over monotherapy on ureteral stent-related symptoms – outcome from a randomized controlled trial. Issue 1 (December 2016) - Liu, Qinyu; Liao, Banghua; Zhang, Ruochen; Jin, Tao; Zhou, Liang; Luo, Deyi; Liu, Jiaming; Li, Hong; Wang, Kunjie
Abstract Background Controversy remains on the superiority of combination therapy over monotherapy on ureteral stent-related symptoms (SRSs). We tend to explore if there is a necessity of combination therapy. Methods One hundred cases of unilateral upper urinary tract calculi with stent insertion (pre and post flexible ureteroscopy) were randomized into 4 groups, given non-treatment, solifenacin, tamsulosin or combination respectively. Eight times of follow-ups were given after each insertion. Results SRSs released spontaneously within 4 days after insertion (p = 0.017) but then stay with no further improvement. Benefit of solifenacin on flank pain started showing after day4 (p = 0.002), which was comparable to that of tamsulosin and combination (p = 0.914 vs 0.195). Combination therapy showed superiority over both monotherapy before day4, but after then solifenacin and tamsulosin showed similar effectiveness with the combination therapy on both bladder pain (p = 0.229 vs 0.394) and urgency (p = 0.813 vs 0.974). No improvement on hematuria or frequency was observed in each group. Conclusions Combination therapy takes effect faster but shows no supervisory after the first few days compared with monotherapy. Trial registration The study protocol was registered on Chinese Clinical Trial Register on April 17th, 2013 (registration number:ChiCTR-TRC-13003148 ).